Histological Changes Associated with the Graft Union Development in Tomato - Carlos Frey; José Luis Acebes; Antonio Encina; Rafael Álvarez (Plants, 2020)
Despite the importance of grafting in horticultural crops such as tomato (Solanum lycopersicum L.), the structural changes that occur during the graft establishment are little understood. Using histological techniques, the present work examines the time course of changes on the anatomical structure of the graft junction in functional tomato homografts and compares it to that of heterografts and non-functional grafts. No apparent differences were detected between homo- and heterografts, showing similar tissue development. At 10 days after grafting, the cell walls of the scion and rootstock in the area of the graft junction were thicker than usual. Undifferentiated cells and new vascular tissue emerged from the pre-existing vasculature. Adventitious roots appeared mainly on the scion, arising from the pre-existing vasculature. At 20 days, more pronounced vascular tissue was visible, along with large areas showing vascular connection. At 210 days, vestiges of the changes undergone in graft development were still visible. Generally, non-functional grafts presented layers of necrotic remains and deposition of cell wall material in the cut edges, impeding the suitable scion-rootstock connection. Our results show that accurate changes in pre-existing vasculature and the cell walls of the adhesion line are crucial to the development of functional grafts.